Retail prices for selected items 1997-2006 - Nigeria, National bureau of Statistics (Abuja, Nigeria : National bureau of Statistics, 2007)
The publication is a compilation of retail prices of selected items by states, zone, selected cities and national levels.
oif 07/02/2020
Ref.
Keywords: Consumer price indexes; Prices; Food prices; Consumer goods--Prices; Nigeria